CATCH: high specific transcriptome-focused fusion gene variants discrimination. Issue 55 (22nd June 2022) - Yuan, Rui; Bai, Xiaopeng; Hu, Xiaolin; Zhang, Hong; Hou, Changjun; Long, Quanxin; Luo, Yang
Abstract : A CRISPR-Cas13a triggered catalytic hairpin assembly (CATCH) approach for accurate and impartial identification of fusion gene variants. Abstract : We develop a CRISPR-Cas13a triggered catalytic hairpin assembly (CATCH) approach for accurate and impartial identification of variants by integrating the fusion gene-selected recognition of CRISPR-Cas13a with collateral cleavage-assisted catalytic hairpin assembly amplification. This approach achieved an accuracy of 100% in a pilot experiment involving 34 clinical samples.